A LITERATURE REVIEW ON TEACHER STRATEGIES TO ENHANCE SPEAKING SKILLS OF ELEMENTARY SCHOOL STUDENTS IN INDONESIAN LANGUAGE EDUCATION - Juang Kurniawan (CV. Fahr Publishing, 2025)
This study aims to identify and synthesize effective teacher strategies in enhancing the speaking skills of elementary school students within Indonesian language learning contexts. Given the limited attention to speaking instruction in mother-tongue education, especially at the primary level, this research employs a literature review method by analyzing 20 peer-reviewed articles published in the last five years. The data were collected through systematic searching, screening, and thematic analysis across major academic databases. The findings reveal that scaffolding, storytelling, role play, group discussion, and digital media are the most frequently used strategies. Among these, scaffolding and storytelling consistently show high effectiveness in developing fluency, confidence, and vocabulary. The study’s novelty lies in its comprehensive mapping of teaching strategies according to grade levels, task types, and speaking components, offering a practical guide for educators. It also highlights the emerging role of digital tools in supporting vocabulary enrichment and interactive engagement in Bahasa Indonesia classes. Furthermore, this research fills a gap by focusing specifically on speaking instruction in elementary Bahasa Indonesia education, which is often underrepresented in the literature. The conclusion affirms that a combination of context-sensitive strategies—tailored to learners' developmental stages and supported by technology where appropriate—can significantly improve speaking outcomes. The results contribute both theoretical and practical insights for teachers, curriculum developers, and educational policymakers seeking to strengthen foundational communication skills in local language instruction.